2001
DOI: 10.1016/s0736-5748(01)00041-7
|View full text |Cite
|
Sign up to set email alerts
|

Brain‐derived neurotrophic factor and TrkB tyrosine kinase receptor gene expression in zebrafish embryo and larva

Abstract: The genes that encode the neurotrophin family of secreted polypeptides and the Trk family of high affinity neurotrophin transmembrane protein tyrosine kinase receptors are induced at the time of neurogenesis in mammals and are known to play critical roles in nervous system development. We show here that in contrast to mammals, the genes encoding the neurotrophin brain-derived neurotrophic factor (BDNF) and the neurotrophin receptor TrkB are expressed throughout embryonic development in the zebrafish. At the em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
55
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(59 citation statements)
references
References 108 publications
(112 reference statements)
4
55
0
Order By: Relevance
“…early stages and in cells lining the gill arches and the jaw cartilages at 4 dpf (Lum et al, 2001). Our data show that BDNF is critical for normal development of the cartilage in the mandibular, hyoid and branchial arches.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…early stages and in cells lining the gill arches and the jaw cartilages at 4 dpf (Lum et al, 2001). Our data show that BDNF is critical for normal development of the cartilage in the mandibular, hyoid and branchial arches.…”
Section: Discussionmentioning
confidence: 59%
“…1, available at www.jneurosci.org as supplemental material). However, as described previously by Lum et al (2001), the detection of mature BDNF was much weaker, so it was not feasible to reliably quantify this band.…”
Section: Htt-mo Phenotype Is Caused By Reduced Bdnf Levelsmentioning
confidence: 85%
See 1 more Smart Citation
“…It is important dur- [Theiss and Güntürkün, 2001] and frog [Duprey-Díaz et al, 2002] tectum and in the hypothalamo-hypophyseal system of Xenopus [Wang et al, 2005]. With regard to teleost fish, BDNF expression has been confirmed in the brain of the southern platyfish [Götz et al, 1992], in the developing zebrafish brain and retina [Hashimoto and Heinrich, 1997;Lum et al, 2001], and in the tench retina [Caminos et al, 1999]. Five neurotrophin receptors have been described in zebrafish [Martin et al, 1995], two of which have been reported to be isoforms of the Trk B receptor and their mRNA is widely distributed throughout the brain and spinal cord of larval zebrafish [Martin et al, 1995].…”
Section: Introductionmentioning
confidence: 98%
“…[22][23][24][25] The nonreceptor tyrosine kinase SRC is involved in egg activation during fertilization, 26 and FAK has a role in cell adhesion and exhibits noncanonical regulatory phosphorylation. 27,28 The MET receptor tyrosine kinase regulates liver and cerebellum development; [29][30][31] the TEC tyrosine kinase is expressed in the zebrafish kidney; 32 the TRKB receptor tyrosine kinase is expressed throughout embryonic development and lacks a kinase domain until neurogenesis; 33 MuSK functions in neuromuscular synapse formation; 34 and PTK7 knockdown results in convergent extension defects. 35 The zebrafish cardiovascular system is profoundly influenced by tyrosine kinases.…”
Section: Tyrosine Kinases In Zebrafishmentioning
confidence: 99%